1999
DOI: 10.1093/oxfordjournals.aje.a010069
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk Factors Clustering Features of Insulin Resistance Syndrome (Syndrome X) In a Biracial (Black-White) Population of Children, Adolescents, and Young Adults: The Bogalusa Heart Study

Abstract: Recently, independent factors representing different features of insulin resistance syndrome (Syndrome X) have been identified by factor analysis in middle-aged and elderly adult populations. In this study, factor analysis was applied to the clustering characteristics of Syndrome X in a biracial (Black-White) community-based population of 4,522 children (ages 5-11 years), adolescents (ages 12-17 years), and young adults (ages 18-38 years) from the Bogalusa Heart Study who were screened during 1988-1996. Ponder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
175
5
6

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(209 citation statements)
references
References 0 publications
23
175
5
6
Order By: Relevance
“…In Table 1 we present 15 papers, [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] all of which used different sets of variables, number of criteria and cutoff points to define the risk-factors associated with the MS. [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] The main differences concern the techniques used to estimate adiposity (body mass index (BMI) and/or waist circumference (WC)), and the variable(s) chosen to evaluate glucose metabolism (fasting glucose, …”
Section: Actual Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…In Table 1 we present 15 papers, [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] all of which used different sets of variables, number of criteria and cutoff points to define the risk-factors associated with the MS. [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] The main differences concern the techniques used to estimate adiposity (body mass index (BMI) and/or waist circumference (WC)), and the variable(s) chosen to evaluate glucose metabolism (fasting glucose, …”
Section: Actual Featuresmentioning
confidence: 99%
“…12 Nonetheless, the three proposed definitions have been used in several studies carried out in pediatric populations, which reported high-prevalence of the MS in obese children and adolescents. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] The results of these studies varied according to the selected diagnostic criteria used, as established by a recent comparison study. 34 Moreover, in an evaluation of the different prevalence yields using different definition, Goodman et al 35 found that ATP III definition identified half as many children and adolescents as having MS as did WHO definition in the same population.…”
Section: Introductionmentioning
confidence: 99%
“…While earlier studies in childhood had focused on the clustering of risk factors for cardiovascular diseases [7, 8], recent studies had reported the prevalence of MeS during childhood [911]. Several definitions have been proposed for MeS in children and some of these definitions followed the ATP III guidelines [914].…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Two 10,12 of the three common definitions include measures of insulin resistance, reflecting the proposed causal or mediating role insulin action plays in the development of MS. 13,14 In the paediatric literature there is no single definition of MS. [15][16][17] Barriers to a consistent, accepted definition for children and adolescents include use of adult cut points or a single set of cut points for all ages of childhood, the fact that disturbances seen in the metabolic indicators in most children are quantitatively moderate, lack of a normal range for insulin concentration across childhood, the insulin resistance of puberty, and lack of central obesity (waist) cut points linked to obesity morbidity or MS for children. If hyperinsulinaemia alone is used as a marker of MS in children, 18 it ignores the clustering of several metabolic indicators which is potentially of greater clinical significance.…”
Section: Introductionmentioning
confidence: 99%